ANALISIS RISIKO USAHA PEMBENIHAN IKAN NILA MERAH DI KELOMPOK PEMBUDIDAYA IKAN MINO NGREMBOKO KECAMATAN NGEMPLAK KABUPATEN SLEMA - Andhika, Rio; Setyowati, Nuning; Qonita, Rr Aulia (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2019)
This study analysed the receipts, costs, and expenses received by red tilapia seed farmers, as well as the level of production risk, price risk and expenditure risk in KPI Mino Ngremboko. The basic method used in this research was a descriptive method. This research was conducted at KPI Mino Ngremboko. The selection of research locations was conducted purposively. The sampling method used was the census method. The analysis was carried out using the coefficient of variation method. Research results there were production risks, price risk, and risk of spending on red tilapia at KPI Mino Ngremboko. The sources of risk that arise were high fish seed mortality rates, increased feed prices, and limited land to increase production. Variation coefficient value (CV) of production risk, price risk, income risk were relatively low that showed the hatchery of red tilapia has a low risk. Meanwhile, the L value of price risk, production risk, and expenditure risk were positive results and the value was greater than BEP. The value shows that when the hatchery reaches the lowest point in production, price, and income, farmers still avoid losses.